Characterization of Polyhydroxybutyrate Nanoparticles - Ghafil, Jenan A.; Flieh, May T. (Iraqi Journal of Science, 2022)
Preparation of nanoparticles is one of the important ways to increase the biological effectiveness of materials. There are several methods to prepare the polyhydroxybutyrate (PHB) nanoparticles. Here, a new method is used based on exposing PHB to ultrasound waves under variable pH conditions. In the present study, PHB was added to distilled water and pH was adjusted to 4 by HCl (1 N). The suspension was exposed to ultrasound waves at 4500 kh for 25 seconds. Then, pH was readjusted to 10 by NaoH (1N) and the mixture was incubated for 2 h at 21 oC. Finally, the pH was adjusted to 7 by HCl (1 N) and the mixture was incubated at 21 oC for 18 h. The characterization of the prepared nanoparticles was achieved by using atomic force microscopy (AFM), Fourier-transform infrared spectroscopy (FTIR), ultraviolet (UV) spectrophotometer, X-ray powder diffraction (XRD), and scanning electron microscopy (SEM). The results demonstrated the formation of nanoparticles, especially after examinations by SEM and AFM, which showed that the diameter of particles was between 22.9 and 73.95. The present study confirmed that the method of exposing PHB to gradient pH and high levels of ultrasonic waves could produce PHB nanoparticles.